2004
DOI: 10.1038/nature02733
|View full text |Cite
|
Sign up to set email alerts
|

The homeotic protein AGAMOUS controls microsporogenesis by regulation of SPOROCYTELESS

Abstract: The Arabidopsis homeotic gene AGAMOUS (AG) is necessary for the specification of reproductive organs (stamens and carpels) during the early steps of flower development. AG encodes a transcription factor of the MADS-box family that is expressed in stamen and carpel primordia. At later stages of development, AG is expressed in distinct regions of the reproductive organs. This suggests that AG might function during the maturation of stamens and carpels, as well as in their early development. However, the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
267
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(287 citation statements)
references
References 25 publications
10
267
0
2
Order By: Relevance
“…This increase in WUS expression in later time points probably reflected a role of AG in the activation of WUS expression in anthers and carpels. The expected changes in the expression of APETALA1 and SPOROCYTELESS, two known AG targets (Ito et al, 2004), showed that AG activity was being effectively activated by our treatments (see Supplemental Figures 4B and 4C online).…”
Section: Ag Binds the Wus Locus In Vivo And Directly Represses Wus Exmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in WUS expression in later time points probably reflected a role of AG in the activation of WUS expression in anthers and carpels. The expected changes in the expression of APETALA1 and SPOROCYTELESS, two known AG targets (Ito et al, 2004), showed that AG activity was being effectively activated by our treatments (see Supplemental Figures 4B and 4C online).…”
Section: Ag Binds the Wus Locus In Vivo And Directly Represses Wus Exmentioning
confidence: 99%
“…This indicates that AG was able to directly repress WUS expression. We were aware that a previous study using 35S:AG-GR ag-1 inflorescences containing flower buds of stages 1 to 10 showed that AG induction activated WUS expression at 8 h postinduction (Ito et al, 2004). To reconcile these results, we monitored WUS expression in a postinduction time course (0 to 24 h).…”
Section: Ag Binds the Wus Locus In Vivo And Directly Represses Wus Exmentioning
confidence: 99%
“…In spl/nzz mutants, development of both male and female reproductive organs proceeds normally until the ACs are formed, but the ACs fail to differentiate into sporocytes. Subsequently, SPL was found to be the target of regulation by the floral homeotic gene AGAMOUS (AG) [3]. AG is a floral organ identity gene required for the specification of stamens and carpels in the third and fourth whorls of the flower [4].…”
mentioning
confidence: 99%
“…AG is a floral organ identity gene required for the specification of stamens and carpels in the third and fourth whorls of the flower [4]. AG encodes a transcription factor of the MADS-box family expressed in stamen and carpel primordia, and is required for the activation of SPL expression [3]. In anthers, there are additionally two leucine-rich repeat receptor-like protein kinases, BARELY ANY MERISTEM1 (BAM1) and BAM2, that act in a regulatory loop with SPL to promote somatic cell types and to restrict SPL expression to the inner region of the locule [5].…”
mentioning
confidence: 99%
“…Many genes have been shown to be linked to anther and pollen development in Arabidopsis. Anther development begins with the induction of the transcription factor NOZZLE/SPOROCY-TELESS (NZZ/SPL) by AGAMOUS (AG), an important MADS box transcription factor responsible for the formation of stamens and carpels in the third and fourth whorls of the wild-type (WT) flower [10]. NZZ/SPL, which shows homology to MADS-like transcription factors and plays an important role during archesporial division, is required for the initiation of sporogenesis during both stamen and carpel development.…”
mentioning
confidence: 99%